AVALIAÇÃO DA ATIVIDADE DE SUPRIMENTOS EM ORGANIZAÇÕES HOSPITALARES - Pinto, Geraldo Luiz de Almeida (2004)
This study has as purpose evaluating supply process on hospital organizations, a market segment where activities costs are important but its management does not follow the best market practices towards costs reduction and warranty of appropriate services. In function of theoretical specific study absence, was drawn up a concept model, presenting as basis techniques established on the market, showing and defining necessary functions to operational activities execution and decisions on hospital supply activities, setting up its partnerships to structure them as process and choosing a set of best practices that allows to make technique and management analysis. From developed model and the best practices established was drawn up a research questionnaire directed to a definite group of hospitals in order to make a diagnosis of supply level which results show that despite of organizations management admit the importance of supply activities there are considerable gaps between the visions of what is important to be done and what is really done, allowing identify priorities to improve supply process.